FAMILY ROLE IN FULLFILLMENT PERSONAL HYGIENE NEEDS OF THE ELDERY - Juliati Koesrini; Apriyani Puji Hastuti; Erlia Dwi Agustia; Bayu Budi Laksono; Amin Zakaria (Indonesian Journal Of Empirical Nursing Sciences, 2024)
The aging process in the eldery will affect a person’s level of independency. It means that eldery no longer take care of themselves, in this case the eldery were very dependent on their families. The role of the family it selfis highly expected by eldery to assisst in their family needs. The aim of this study was to describe the role of the family in the fullfillment of personal hygiene in the eldery in Pasuruan Regency. The design of this study used descriptive study with cross - sectional approaches. The population of study are eldery families and use total sampling were 80 respondent. The research location is in Pasuruan Regency on April 2024. Variables of this study was family role in fulfillment personal hygiene needs of the eldery. Instruments of this study using questionnaire. Analysis of this study used univariate analyzed. The results of this study shows that the role of family in fulfillment personal hygiene in the eldery in Pasuruan Regency with 80 respondent. It was found that the most of them had a good family role in 55% and 45% had a sufficient family role in fulfillment personal hygiene needs in eldery. These results are influenced by several factors age, education, knowledge, occupation, gender. Based on this research, it can motivate that early adult women can develop a positive self - concept so that they will create satisfaction with their positive body image and positive coping mechanisms